Prognostic role of procalcitonin in ST-elevation myocardial infarction complicated by cardiogenic shock. (October 2021) - Sharma, Yash Paul; Kasinadhuni, Ganesh; Santosh, Krishna; Parashar, Nitin Kumar; Sharma, Rakesh; Bootla, Dinakar; Kanabar, Kewal; Krishnappa, Darshan
Objective: Cardiogenic shock accounts for the majority of deaths amongst patients with ST-elevation myocardial infarction. Procalcitonin is elevated in acute myocardial infarction, especially when complicated by left heart failure, cardiogenic shock, resuscitated cardiac arrest, and bacterial infections. However, the prognostic utility of procalcitonin in ST-elevation myocardial infarction complicated by cardiogenic shock has not been systematically evaluated. Methods: We performed a retrospective registry review of 125 patients with ST-elevation myocardial infarction and cardiogenic shock over 2 years at a tertiary referral hospital to examine the prognostic value of serum procalcitonin measurement at 24 hours after the onset of infarction for in-hospital mortality. Results: The mean age of the study population was 57.75 ± 11.1 years, and the median delay from onset to hospital admission was 15 hours. The in-hospital mortality was 28.8%. Receiver operating characteristic analysis revealed a strong relationship between elevated procalcitonin and in-hospital mortality (area under the curve = 0.676; p = 0.002). Although procalcitonin was found to be higher in non-survivors in univariate analysis, it was not an independent predictor of mortality in multivariate regression analysis. Acute kidney injury, left ventricular ejection fraction, and non-revascularization were independently associated with mortality after adjusting for covariates. Conclusion: Although procalcitonin was higher in non-survivors, static procalcitonin measurement at 24 hours after the onset of ST-elevation myocardial infarction complicated by cardiogenic shock was not an independent predictor of in-hospital mortality. Additional prospective studies are required to assess the role of serial procalcitonin monitoring in ST-elevation myocardial infarction complicated by cardiogenic shock.